High-resolution structures of a thermophilic eukaryotic 80S ribosome reveal atomistic details of translocation - Kišonaitė, Miglė; Wild, Klemens; Lapouge, Karine; Ruppert, Thomas; Sinning, Irmgard (Nature Communications, 2022)
Ribosomes are complex and highly conserved ribonucleoprotein assemblies catalyzing protein biosynthesis in every organism. Here we present high-resolution cryo-EM structures of the 80S ribosome from a thermophilic fungus in two rotational states, which due to increased 80S stability provide a number of mechanistic details of eukaryotic translation. We identify a universally conserved ‘nested base-triple knot’ in the 26S rRNA at the polypeptide tunnel exit with a bulged-out nucleotide that likely serves as an adaptable element for nascent chain containment and handover. We visualize the structure and dynamics of the ribosome protective factor Stm1 upon ribosomal 40S head swiveling. We describe the structural impact of a unique and essential m1acp3 Ψ 18S rRNA hyper-modification embracing the anticodon wobble-position for eukaryotic tRNA and mRNA translocation. We complete the eEF2-GTPase switch cycle describing the GDP-bound post-hydrolysis state. Taken together, our data and their integration into the structural landscape of 80S ribosomes furthers our understanding of protein biogenesis.